A Manual for Gender Audit Facilitators : the ILO Participatory Gender Audit Methodology. - Office, International Labour (International Labour Office, 2007)
This manual provides gender audit facilitators with guidelines and practical instructions on how to plan and implement participatory gender audits in an organizational context. Structured chronologically, the manual is a step-by-step guide that provides the facilitators with a set of tools that help examine the extent to which equality is being institutionalized; identify good practices in technical work and point to effective and efficient ways of moving forward in mainstreaming gender in all work activities, thereby supporting an organization's commitment to gender equality.